2018
DOI: 10.3390/ani8090154
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Social Desirability Bias in Perceptions of Dog Adoption: All’s Well that Ends Well? Or Does the Method of Adoption Matter?

Abstract: Simple SummaryDog adoption is often cited as an ethical and popular method of acquisition but interpretation of the term ‘adoption’ may vary. In a nationally representative survey of the U.S., 767 respondents were asked questions regarding their opinions of dog acquisition including adoption. Within the sample, 45% had a dog; of those, 40% had adopted a dog and 47% visited a veterinarian once a year. Respondents’ preferences for the most ethical method of dog adoption were elicited using a survey instrument. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
3
15
1
1
Order By: Relevance
“…Similarly to the 54% of respondents who used heartworm prevention in this study, Bir et al [14] found that 55% of dog owners used heartworm prevention continuously in their nationally representative study of U.S. residents. Other studies have found heartworm preventative use compliance of less than 50% [39,40].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly to the 54% of respondents who used heartworm prevention in this study, Bir et al [14] found that 55% of dog owners used heartworm prevention continuously in their nationally representative study of U.S. residents. Other studies have found heartworm preventative use compliance of less than 50% [39,40].…”
Section: Discussionsupporting
confidence: 66%
“…For both dog and cat owners, common acquisition methods selected by pet owners were purchased, or adopted/rescued. Similar to these findings, in their representative sample of U.S. residents, Bir et al [14] found that 37% of dog owners had purchased a dog, and 40% of dog owners had adopted a dog. In a best-worst scaling experiment of the most ethical ways to acquire a dog, Bir et al [15] found that adoption had by far the largest preference share (79%) when compared to other methods including purchasing, finding a stray, gift, or others.…”
Section: Discussionmentioning
confidence: 54%
“…The sample is also overeducated as a whole. It is common for samples recruited online to oversample relatively well‐educated individuals, as people with lower educational attainment may have less internet access (Bir, Widmar, & Croney, 2018; Cummins, Widmar, Croney, & Fulton, 2015). Finally, respondents from the South are over‐represented in the sample, while the West is underrepresented.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the existence of commercial breeding kennels in the US reflects both the increasingly high demand for pet dogs that needs to be met, the inability of small-scale breeders, shelters and rescues to do so, and socio-ethical factors that support such enterprises, particularly when demand is high but supply is limited. These include the need to avoid infringements on the public's right and expressed desire to retain choices in where they acquire dogs, inequities in accessing dogs that meet people's preferred characteristics, and creation of black markets for dogs that further jeopardize their welfare [1,4,5].…”
Section: Introductionmentioning
confidence: 99%